2012
DOI: 10.1080/07055900.2012.715078
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Freshening in the Northwest Pacific Subtropical Gyre near Luzon Strait

Abstract: Argo observations reveal that the salinity in the North Pacific subtropical gyre near Luzon Strait gradually declined by 0.2 (practical salinity scale used) from 2003 to 2007 over a depth range of 100 m to 200 m. Such freshening is also found in the outputs of the Estimating the Circulation and Climate of the Ocean (ECCO) model. The possible mechanisms for the freshening are investigated using the surface freshwater flux (E-P) data, the ECCO outputs and a salt budget equation for the upper ocean. Our analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…The possible connection between the subtropics and the western boundary via the subsurface salinity propagation in the North Pacific is an important issue and has been recently examined [e.g., Sasaki et al, 2010;Ren and Riser, 2010;Li et al, 2012;Yan et al, 2012Yan et al, , 2013Nagano et al, 2014;Nan et al, 2015]. Some studies suggest that the anomalies originating in the northeastern subtropical Pacific can subduct and penetrate to the subsurface of the northwestern Pacific [e.g., Sasaki et al, 2010;Ren and Riser, 2010;Li et al, 2012;Kolodziejczyk and Gaillard, 2012], but some recent studies, on the other hand, demonstrate that the subsurface salinity anomalies in the northwestern Pacific cannot be traced back to those of the eastern subtropics [Yan et al, 2012[Yan et al, , 2013Nagano et al, 2014;Nan et al, 2015]. Here our study shows the subsurface salinity anomalies on 24.5-25.4 kg m 23 isopycnals in the eastern Luzon Strait exhibit a pronounced negative trend.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The possible connection between the subtropics and the western boundary via the subsurface salinity propagation in the North Pacific is an important issue and has been recently examined [e.g., Sasaki et al, 2010;Ren and Riser, 2010;Li et al, 2012;Yan et al, 2012Yan et al, , 2013Nagano et al, 2014;Nan et al, 2015]. Some studies suggest that the anomalies originating in the northeastern subtropical Pacific can subduct and penetrate to the subsurface of the northwestern Pacific [e.g., Sasaki et al, 2010;Ren and Riser, 2010;Li et al, 2012;Kolodziejczyk and Gaillard, 2012], but some recent studies, on the other hand, demonstrate that the subsurface salinity anomalies in the northwestern Pacific cannot be traced back to those of the eastern subtropics [Yan et al, 2012[Yan et al, , 2013Nagano et al, 2014;Nan et al, 2015]. Here our study shows the subsurface salinity anomalies on 24.5-25.4 kg m 23 isopycnals in the eastern Luzon Strait exhibit a pronounced negative trend.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In recent years, salinity observations, especially the subsurface salinity observations, are made available from the Argo profiling floats [ Roemmich et al ., ]. The rapid growing of salinity data set has fueled many interests to resolve the subsurface salinity variability and its propagation in the North Pacific [e.g., Sasaki et al ., ; Ren and Riser , ; Li et al ., ; Yan et al ., ; Nagano et al ., ; Nan et al ., ; Nagano et al ., ]. For example, using the gridded product of temperature and salinity from Argo during the period of 2001–2008, Sasaki et al .…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Ocean salinity observations, in particular subsurface salinity observations, are recently made available from Argo profiling floats (Roemmich & Steering, ). The growth of Argo observations in terms of spatial‐temporal coverage, combined with more than 50 years of repeating hydrographic observations along the 137°E section from the Japan Meteorological Agency, allows to resolve the subsurface salinity variability in the North Pacific (e.g., Li et al, ; Nagano et al 2015; Nan et al, ; Ren & Riser, ; Sasaki et al, ; Yan et al, , , ). For instance, based on Argo salinity from 2001 to 2008, Sasaki et al () found the salinity anomalies along the isopycnals were generated and subducted in the northeastern subtropical North Pacific (120–150°W), and these anomalies could then be advected southwestward to the western boundary and equatorial regions by the mean geostrophic current.…”
Section: Introductionmentioning
confidence: 99%